Drug Safety in Developing Countries: Achievements and Challenges - Al-Worafi, Yaser Mohammed (Academic Press, 2020)
About the book Key Features Provides a single resource for educators, professionals, researchers, policymakers, organizations and other readers with comprehensive information and a guide on drug safety related issues Describes current achievements of drug safety practice in developing countries Addresses the challenges of drug safety in developing countries Provides recommendations, including practical ways to implement strategies and overcome challenges surrounding drug safety Description Drug Safety in Developing Countries: Achievements and Challenges provides comprehensive information on drug safety issues in developing countries. Drug safety practice in developing countries varies substantially from country to country. This can lead to a rise in adverse reactions and a lack of reporting can exasperate the situation and lead to negative medical outcomes. This book documents the history and development of drug safety systems, pharmacovigilance centers and activities in developing countries, describing their current situation and achievements of drug safety practice. Further, using extensive case studies, the book addresses the challenges of drug safety in developing countries.